2003
DOI: 10.1002/14651858.cd001244
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory amino acid antagonists for acute stroke

Abstract: CNS1102-003 {published data only} * Block GA. Final results from a dose-escalating safety and tolerance study of the non-competitive NMDA antagonist CNS1102 in patients with acute cerebral ischemia. Stroke 1995;26:185. Fisher M. Cerestat (CNS 1102), a non-competitive NMDA antagonist, in ischemic stroke patients: dose-escalating safety study. Cerebrovascular Diseases 1994;4:245. McBurney RN. Development of the NMDA ion-channel blocker, aptiganel hydrochloride, as a neuroprotective agent for acute CNS injury. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 68 publications
(1 reference statement)
0
53
0
7
Order By: Relevance
“…529 A systematic review of the trials testing these medications found no improvements in rates of either death or favorable outcomes with treatment. 530 Neither fosphenytoin nor sipatrigine has demonstrated effectiveness in treatment of acute stroke. 531,532 Repinotan, a serotonin agonist, has shown some promise in preliminary studies.…”
Section: Neuroprotective Agentsmentioning
confidence: 99%
“…529 A systematic review of the trials testing these medications found no improvements in rates of either death or favorable outcomes with treatment. 530 Neither fosphenytoin nor sipatrigine has demonstrated effectiveness in treatment of acute stroke. 531,532 Repinotan, a serotonin agonist, has shown some promise in preliminary studies.…”
Section: Neuroprotective Agentsmentioning
confidence: 99%
“…[739][740][741][742][743][744][745][746][747][748][749][750][751][752] A 2003 systematic review of the excitatory amino acid modulator trials found no rates of improvements in either death or favorable outcomes with treatment. 753 Lubeluzole, which is thought to downregulate the glutamate-activated nitric oxide synthase pathway, was tested in several clinical trials, including one that evaluated the combination of the medication and intravenous rtPA. 754 Although a pilot study suggested safety and a reduction in deaths, subsequent larger clinical trials found no effects in reducing deaths or improving outcomes after stroke.…”
Section: Pharmacological Agentsmentioning
confidence: 99%
“…However, no clear therapeutic efficacy was observed. 21,43,44 This spectacular lack of success has led to a massive decline in drug discovery research in the area of stroke and traumatic brain injury. This may change if efficacy is observed with compounds currently in clinical trial for stroke, e.g., Cerovive (NXY-059).…”
Section: Drugs For Neurodegenerative Disordersmentioning
confidence: 99%